Magnetic Field Dipolarization and Its Associated Ion Flux Variations in the Dawnside Deep Inner Magnetosphere: Arase Observations. Issue 16 (17th August 2018) - Nosé, M.; Matsuoka, A.; Kasahara, S.; Yokota, S.; Teramoto, M.; Keika, K.; Yamamoto, K.; Nomura, R.; Fujimoto, A.; Higashio, N.; Koshiishi, H.; Imajo, S.; et al.
Abstract: The Arase satellite observed clear dipolarization signatures at r ~4.3–4.6 R E, GMLAT~16°–18°, and MLT~5.5–5.7 hr around 15:00 UT on 27 March 2017 when Dst ~−70 nT. Strong magnetic field fluctuations were embedded and their characteristic frequency was close to the local gyrofrequency of O + ions. After the dipolarization, O + flux was enhanced at ≤15 keV, while H + flux showed no clear variations. These observations provide evidence for the direct supply of O + ions from the ionosphere. There were no clear signatures for the nonadiabatic local acceleration of O + ions. We consider that a bump‐on‐tail structure in the energy spectrum around 30–50 keV due to a combination of charge exchange loss and drift motion of ions masks the nonadiabatic acceleration. Occurrence of the magnetic field dipolarization at dawn, which is far from the well‐known premidnight occurrence peak, may be due to an eastward skewing of partial ring current during the storm main phase. Plain Language Summary: The Exploration of energization and Radiation in Geospace (ERG) "Arase" satellite was launched by Japan Aerospace Exploration Agency on 20 December 2016. Arase was placed in an elliptical orbit having initially a perigee of ~460‐km altitude and an apogee of 6.0 R E to survey the inner magnetosphere. This unique orbit makes it possible for Arase to successfully observe a clear magnetic field dipolarization and its associated ion flux variations in the dawnside deep inner magnetosphere, which have not been reported in previous studies. Observations provide evidence for the direct supply of O + ions from the ionosphere to the deep inner magnetosphere. Occurrence of the magnetic field dipolarization at dawn, which is far from the well‐known premidnight occurrence peak, may be due to an eastward skewing of partial ring current during the storm main phase. Key Points: Magnetic field dipolarization was observed by the Arase satellite at r ~4.3–4.6 R E and dawn during the 27 March 2017 storm The dipolarization was accompanied by strong magnetic fluctuations and O + flux enhancements at ≤15 keV Occurrence of the dipolarization at dawn may be due to an eastward skewing of partial ring current during the storm main phase